Monitoring of complex forming of the active pharmaceutical substance and β-cyclodextrin as an additive of the mobile phase using mass spectrometry - Milenković Anđela; Miljić Dragana; Mitrović Jelena; Protić Ana; Otašević Biljana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2016)
In recent years, there is aim to reduce toxic solvents use in chromatographic techniques. Beta-cyclodextrins (β-CD) are commonly used for this purpose, as substance retention modulators. By increasing their concentration in the mobile phase, generally there is a decrease in analyte retention time, and consequently, a decrease in the organic solvent ratio in the mobile phase. The aim of this study was to investigate β-CD and selected sartans inclusion complexes formation. The emphasis was on the influence of the aqueous phase pH value, the drug-β-CD molar ratio and the organic solvent type on complex formation. The mass spectrometry investigation included characterization of the formed complex drug: β-CD at different molar ratios (1:1, 1:2, 1:5 and 1:10), and at different pH values of the aqueous phase (5, 7 and 9) using triple quadrupole mass analyzer. The mobile phase and solvent in which the complexes were formed consisted of acetonitrile and water mixture (50:50, v/v) and methanol and water mixture (50:50, v/v). Measurements of these complexes signal intensity after electrospray ionization in negative mode. Observed m/z values indicated formation of drug-β-CD in 1:1 ratio at all pH values of water phase and independently of organic solvent type and β-CD ratio. It was noted that formed complex signal intensity increased only by increasing β-CD ratio.